INTERDISCIPLINARITY AS THE MAIN VECTOR FOR THE DEVELOPMENT OF ENGINEERING EDUCATION (Network Conference Review) - Vasily G. Ivanov; Alla A. Kaybiyaynen; Mansur F. Galikhanov (Moscow Polytechnic University, 2016)
The article describes the organizing and holding experience of the International Network Conference «Interdisciplinarity in Engineering Education: Global Trends and Management Concepts - SYNERGY », arranged in six Russian cities and Kazakhstan. There is explained the necessity of interdisciplinary teaching as an innovative form of project engineering education aimed at improvement of training quality and further professional development of engineering staff, summed up the network and final sessions of the conference.